Fathering Daughters and Personality - Max van Lent (Institute of Labor Economics (IZA), 2022)
The big five personality traits develop over a person's lifetime. There is some suggestive evidence that major life events - such as getting married, being fired from a job, and having children - affect personality. However, these associations cannot be interpreted as causal. This is the first paper that studies the causal effect of a life event - the gender of the first-born child - on the big five personality trait scores of fathers. Using yearly longitudinal data (2008 - 2020) I find that having a first-born daughter instead of son increases fathers' extraversion. The gender of the first child also affects labor market outcomes for fathers. Fathers of first-born daughters earn 127 euro more per month (i.e. 6.9% of the average monthly wage). This effect is not driven by changes in the number of hours worked or job switches.
Keywords: J12; J13; J16; J24; 330; family structure; fertility; life events; human capital; big five personality traits; labor market outcomes